(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the formation of the Kazan Turcology School in the 19th century, its development, and the scholarly legacy of its founders. It traces how Kazan University became a major center of Turkic and Oriental studies, with special emphasis on the Halfin dynasty and prominent scholars, analyzing their contributions in depth. The study also explores the school’s impact in both the Russian Empire and the broader Turkic-speaking world.